“THREE-DIMENSIONAL RECONSTRUCTION OF A COMPLEX IATROGENIC DEFECT: AN INTERDISCIPLINARY ORTHODONTIC AND AUGMENTATION STRATEGY” - Ilyasov Abusupyan,; Gadisova Irayganat Gamidovna,; Ortikova Nargiza Khayrullayevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Despite the huge popularity of using dental implants in the practice of a dentist, the number of complications and risks associated with their use still remains at a fairly high level. In some cases, the causes of the formation of gingival-alveolar defects, especially in the aesthetic field, are precisely iatrogenic errors by doctors who do not ensure the proper quality of implantation and augmentation procedures.